(untitled) (Al-Qamar, 2020)
In the word of Urdu literature and poetry, women are seen creating masterpieces of literature beside men but poetic work of women failed to claim as much recognition as of male writers. Most of the part of Classical poetic work of women writers has been lost under the dust of time. Whatever poetic work of female poetesses, we find mentioned in classical poetic testimonies, is very short. It is because of the fact that bulk of women poetry is either spoiled or not considered up to the mark to be valued in male dominated society of that time. In spite of all these adverse circumstances, somehow female poetic tradition continued intermittently. It is also worth mentioning here that in a Muslim society where religion is the pivot of people, presentation of mysticism and religious elements in female poetic works is quite natural. That’s why poetic works of elite class ladies as well as of prostitutes, is the depiction of religious thoughts but these elements are very bantam one. As the religious elements are the subject of very close association for human being, so their analysis is very necessary. That’s why in poetic tradition of nineteenth century, these elements are seen very frequent. In poetic work of Parveen Shākir, one of the famous poetesses of modern time, these religious elements, attitudes and trends are seen but here these are permeated with universal thought of social, class, creed and humanity. In this paper poetic work of Parveen Shākir has been analyzed in connection to old female poetic tradition of classical era.